Evaluation of pediatric admissions for sensitive conditions to Primary Care at University Hospital Alcides Carneiro: Cross-sectional studies (Research, Society and Development, 2025)
Objective: To analyze the clinical and epidemiological profile of ACSC in pediatrics and associated factors, at the Hospital Universitário Alcides Carneiro – HUAC/UFCG, in Campina Grande, Paraíba, Brazil. Method: This is a cross-sectional study carried out with a sample of pediatric patients admitted to HUAC/UFCG. The outcome of the study was “Admission for Primary Care Sensitive Conditions – ICSAP”, obtained from the clinical diagnoses present in the Hospital Admission Authorization (AIHs) and/or Medical Records. The independent variables were: sociodemographic conditions; the Attributes of Primary Health Care (PHC); the trajectory of care. Data collection was done through interviews and a standardized questionnaire. Descriptive and inferential statistical analyzes were used. Results: Among the 43 hospitalizations evaluated, 04 (9.3%) were classified as ACSC. Regarding the association between sociodemographic variables and ICSAP, it was noted that the variables that were associated were “Main Caregiver”, “Mother’s Education” and “Number of Children”. In relation to PHC Attributes, it was observed that Longitudinality was associated with ICSAP, especially in the items: being the same Doctor/Nurse caring for the child in outpatient care and the fact that these professionals know the complete medical history of these children hospitalized for CSAP. Conclusions: the results show that sociodemographic variables, PHC attributes and the journeys taken by the family to hospital admission are important factors in the assessment of ACSC.